"No próximo, desce!": o transporte clandestino na zona sul de São Paulo (1989-2004) - Couto, Eduardo Castro (2009)
This work examines how social relations among workers identified as perueiros involved with informality work in the public transport in the south region of São Paulo from 1989 to 2004 were constituted. Besides, this study tries to understand if the phenomenon of legal transport has contributed to the transformation of the urban space from this area of the city. The south area of São Paulo is one of the most populous areas in the district. The neighborhoods that are part of this region present a series of striking contrasts in the life of its inhabitants which are generally marked by the absence total or partial of social rights for the poor population. On the other hand, there are neighborhoods for the most privileged classes (medium and upper middle class) with housing and luxury condominiums and in some situations delimiting a fragile line with poverty and misery that live nearby. The period proposed for this research is characterized by the advancement of neoliberalism, deregulation of world economies and the growth of informality in the labor market. In order to understand how relationships of dispute and power for the right to circulation and the tensions resulting from the phenomenon of informality in this region sources such as the narratives of the informal workers that took part in this experience, the production of scholars about public transport and public politics for the transport in São Paulo were used